Fostering Student Engagement through Deep Learning in Vocational English Teaching - Madya Giri Aditama; Suwarna Suwarna; Dwiyanto Djoko Pranowo; Bagiya Bagiya; Utomo Utomo (PT. Mifandi Mandiri Digital, 2025)
This qualitative phenomenological study investigates how deep learning-based instructional strategies enhance teacher competence and student engagement in vocational English classrooms at SMK Muhammadiyah Batang. Four English teachers participated in in-depth interviews, classroom observations, and document analysis to explore their lived experiences in implementing Multimedia Teaching Modules (MTM) enriched with kearifan lokal (local wisdom). The modules integrated cultural elements such as traditional batik motifs, local tourism videos, and regional proverbs into vocabulary, speaking, and project-based learning activities. Findings reveal that teachers developed stronger pedagogical competence in designing contextually relevant and culturally responsive lessons. Students showed notable improvement in engagement indicators, including increased participation in discussions, higher on-time assignment submission rates, and enhanced language output in collaborative tasks. Comparative engagement data indicated a clear rise in active learning behaviors post-MTM integration. The cultural contextualization of materials fostered both a sense of identity and greater motivation among learners, making lessons more meaningful and relatable. The discussion situates these findings within the broader framework of deep learning pedagogy, emphasizing its capacity to connect cognitive skills with socio-cultural relevance in vocational education. The study concludes that combining deep learning principles with multimedia and local wisdom can bridge the gap between curriculum objectives and real-world communicative needs in vocational contexts. Recommendations include ongoing teacher training in culturally grounded digital pedagogy and fostering professional learning communities to sustain innovation in English language teaching.